Mobility Management in Cognitive Radio Vehicular Cellular Networks - Ahmed Elbendera, Samar; Mohammed Ghuniem, Atef (International Journal of Engineering and Technology, 2018)
There is a growing interest in enhancing cellular network support for vehicular communication. Cellular networks based on cognitive radio (CR) technology offer a promising solution for both improving the network capacity in areas facing high customer density and achieving matching between costs and demand in areas of low customer density. In this paper, we propose a mobility management technique for CR cellular network in vehicle-to-infrastructure (V2I) scenarios. The management scheme consists of intercellular resource allocation, and spectrum and user mobility management techniques. In the intercellular resource allocation, each cell selects an extended area band to support the mobility of high-speed users and improve cell capacity. Through the spectrum mobility management, both user and target cell selections are decided based on spectrum availability and user mobility. The user mobility management determines the handoff mechanism at different boundaries of the cell that supports good and reliable communications for high speed mobile users. Simulation results show that our scheme outperforms classical handoff schemes in supporting the mobility and the reliable communications in CR cellular networks.
Keywords: cognitive radio; handoff; secondary user; spectrum pool; vehicle-to-infrastructure